(untitled) (Corte Madera, 1997)
Perl is the scripting language used by most people seetting up their own Web servers. This book gives Perl programmers everything needed to write professional scripts and solve practical problems in an easy-to-use, topic-organized format. It provides more than 100 real-life programming situations and their solutions.
Keywords: Perl (ngôn ngữ chương trình máy tính),Perl (Computer program language)